Depositional and Diagenetic Models of Miocene Parigi and Pre-Parigi Carbonates Offshore Northwest Java, Indonesia - Fransiskus J. Sugiaman (Berita Sedimentologi, 1998)
An integrated approach to understanding the deposition and diagenesis of the Parigi carbonates in KL area and the Pre-Parigi carbonates in APN area has been developed using petrographic, well logs and seismic analysis.